Construction of algorithms to automatically determine individual indicators when assessing the shape quality of cross-wound packages - Nuriyev, Mahammadali; Jabbarova, Ganira (Eastern-European Journal of Enterprise Technologies, 2019)
The paper addresses issues related to the selection of individual indicators to estimate the shape quality of cross-wound packages, as well as the construction of algorithms to determine them automatically. We have developed a method for evaluating the quality of shape of cross-wound packages based on the integrated indicator. To substantiate individual indicators, an expert poll was performed to rank defects in the shape of packages according to the degree of their influence on the suitability of packages for processing at subsequent technological transitions. To quantify each of the specified defect in the shape of a bobbin, we defined individual indicators that make it possible to quantify their impact. We have developed decisive rules and algorithms to calculate them based on the earlier obtained array of data on the coordinates of points at the bobbin’s surface. We have determined a score-based estimate of the influence of each indicator, which characterizes defects in winding, on the suitability of packages for processing at subsequent technological transitions. A comprehensive assessment of the package shape could be obtained using a method of weighted index. The mean weighted index is constructed as a dependence whose arguments are the individual quality parameters and their weighted parameters. Given this, we derived a dependence to calculate the integrated quality indicator of the bobbin’s shape. The higher the value for this indicator, the higher the quality of the controlled package. We have assessed the applicability of the constructed integrated quality indicator to analyzing the shape of packages. To this end, we analyzed a batch of packages, which confirmed the reproducibility of the process of analysis of the package shape using the proposed integrated indicator; as well as correspondence between estimates, derived using the proposed procedure, and visual assessments. A method for the integrated quantification of package shape makes it possible to conduct optimization experiments and to assign, based on them, such adjustable parameters for winding mechanisms that would ensure that packages of the required quality are received. The process of designing new winding equipment could be based on the necessary means to regulate a winding process